Response of CHOP therapy in the treatment of Non-Hodgkins Lymphoma - one year study in CMH, Dhaka (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: The lymphomas are a group of malignant disease that originate from uninhibited growth of cellular elements normally found in lymphatic tissue. All forms of lymphoma have the potential to spread from their origin in a single node or chain of nodes to other nodes and eventually to disseminate to spleen, liver and bone marrow. Objective: To assess the response rate and to evaluate the toxicity and safety of CHOP regimen. Methods: In this study 50 cases were selected of all age irrespectively and both sexes diagnosed at Combined Military Hospital, Dhaka. A prescribed proforma was used for each patient. It included particulars of the patient, history, physical findings, laboratory investigations (biopsy, cytology, and bone marrow study), ultrasonography and CT-scan in appropriate cases. Results: In this study, starting from July 2009 to June 2010, 50 patients were included. Out of them, 30 patients (60.00%) achieved complete remission, 12 patients (24.00%) had partial remission. Overall responses were 84 percent and 8 patients (16.00%) were non-responder. Two patients (4%) of non-responder died during chemotherapy. Conclusion: In this study a significant number of patients achieved complete and partial remission. The response was rapid and most of the patients achieved complete or partial remission after receiving only 2-3 cycles of therapy. Considering the toxicities, the patients were well-tolerated to CHOP regimen. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22932 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014